(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the socio-pedagogical necessity of preventing internal regulation disorders in preschool children based on an integrative approach. It also highlights the problems associated with the quality of education in the process of introducing digital technologies into the modern education system. The study substantiates the importance of an integrative approach in the pedagogical process and emphasizes that the use of digital technologies, interactive games and multimedia educational tools contributes to the development of children’s emotional stability, self-control and social adaptation skills.